2022
DOI: 10.3390/ijms23147709
|View full text |Cite
|
Sign up to set email alerts
|

Of Mouse and Man: Cross-Species Characterization of Hypertensive Cardiac Remodeling

Abstract: Hypertension is a major public health concern and poses a significant risk for sudden cardiac death (SCD). However, the characterisation of human tissues tends to be macroscopic, with little appreciation for the quantification of the pathological remodelling responsible for the advancement of the disease. While the components of hypertensive remodelling are well established, the timeline and comparative quantification of pathological changes in hypertension have not been shown before. Here, we sought to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Replacement or scar fibrosis, which involves the formation of fibrotic tissue to replace damaged or necrotic cardiomyocytes [ 71 ], is a common occurrence in CHD models. In hypertension, fibrosis is initiated in the perivascular space [ 72 ], and it has been demonstrated that hypertensive heart disease is characterized by predominant perivascular fibrosis in both human and murine models [ 73 ].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Replacement or scar fibrosis, which involves the formation of fibrotic tissue to replace damaged or necrotic cardiomyocytes [ 71 ], is a common occurrence in CHD models. In hypertension, fibrosis is initiated in the perivascular space [ 72 ], and it has been demonstrated that hypertensive heart disease is characterized by predominant perivascular fibrosis in both human and murine models [ 73 ].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Studies have shown that the increased expression of proinflammatory factors promotes cardiac remodeling. The initiation of the inflammatory response causes the accumulation of extracellular matrix and accelerates the process of myocardial fibrosis ( Cooper et al, 2022 ). Oxidative stress is a key element that affects cardiac remodeling ( Mahmoudi et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HeartJ analysis revealed that human and murine cardiomyocytes are approximately equal in diameter and hypertrophy within a similar range. So far, there is only one publication that directly compares human and murine cardiac hypertrophy, describing different cross sectional areas of cardiomyocytes and degrees of hypertrophy, however, only quantifying cross sections of cardiomyocytes with nuclei [ 15 ]. In general, the relationship between body size and cell size is controversial and complicated by the different use of cell volume, cell cross sectional area, or cell diameter [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%